Hubungan Kebiasaan Belajar Dengan Hasil Belajar IPS Siswa Kelas IV Di Desa Tunjungharjo Kecamatan Tegowanu Grobogan - Islami, Amalia Nur; Pratiwi, Ika Ari; Ismaya, Erik Aditia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The government seeks to realize quality education by improving the quality of human resources through education, in the learning process, supporting facilities and infrastructure are needed in the form of human resources, learning media and the potential of students. The results of interviews with classroom teachers indicate that there are ineffective study habits. Reflected before the learning process, the teacher prepares students and asks students to issue textbooks for the subjects to be studied. The aims of this study are as follows: 1) To examine the relationship between study habits and social studies learning outcomes for fourth grade students in Tunjungharjo Village, Tegowanu District, Grobogan. 2) Describe the relationship between study habits and social studies learning outcomes for fourth grade students in Tunjungharjo Village, Tegowanu District, Grobogan. There is a positive and significant relationship between study habits and social studies learning outcomes for fourth grade students at SDN Tunjungharjo 1 and SDN Tunjungharjo 2, Tegowanu District, which is indicated by a correlation coefficient of 0.641 with a strong level of relationship between study habits and social studies learning outcomes because it is in the 0.60 interval. -0.799 with a contribution of 41.1% and 58.9% influenced by other factors not included in this study. Shown by a correlation coefficient of 0.721 with a strong level of relationship between study habits and learning facilities with social studies learning outcomes because it is in the interval 0.60-0.799 with a contribution of 52% and 48% influenced by other factors not included in this study.